Studying the Effect of Using Rapid Modeling (RP) in Manufacturing Brushes as an Alternative to the Traditional Manufacturing Process - القبيلي خلود (Latakia University Journal -Engineering Sciences Series, 2024)
During this research, We designed lathe bed from two sheets depending on sheets system which used in rapid prototyping, so that we can detective some of aids: reducing the economic effects of the friction and wear in order to achieve the best mechanical properities, and reducing costs of the required materials to make the damaged parts and costs of the maintenance. And taking advantage of Catia program, and finite element method, lathe bed meduim sized, type ZMMC400TN, weight is 700kg, and force is 15KN. We have passed researching in accordance with the following main points: Conduct comparian between two cases of the lathe bed, which the first case is making from Cast iron, and the second case is making from two sheets( depending on Rapid prototyping) steel and cast iron. Conduct comparian between three cases of the lathe bed in terms of deformation, stress distribution on the axis , von misses stress and bed weight which the first case is making from cast iron, and the second case is making from steel and the three case is making from Ipoxy granite. Conduct iconomic comparian between two cases of the lathe bed depending on results of the plans and rapid prtotyping principle. And we have reached the following results: Potential manufacturing the bed from two or more materials according to the number of suggested sheets, and replaced the cast iron with less expensive materials and best mechanic properties. Reducing the friction and wear effects on surface according to the bed material, and reducing the stresses applied on the surface thereby achieve longer life of the bed whithout damage. Achieve saving in maintenance costs of the damaged parts and saving in the time required for maintenance.